Effects of 8 weeks of resistance training in combination with a high protein diet on body composition, muscular performance, and markers of liver and kidney function in untrained older ex-military men - Bagheri, Reza; Shakibaee, Abolfazl; Camera, Donny M.; Sobhani, Vahid; Ghobadi, Hamid; Nazar, Eisa; Fakhari, Hadi; Dutheil, Fred (Frontiers in Nutrition, 2023)
Background: We compared the effects of 8 weeks of RT in combination with either a high (1.6 g/kg/d) or low protein diet (0.8 g/kg/d) on body composition (skeletal muscle mass [SMM] and body fat percentage [BFP]), muscular strength, power, and endurance (upper and lower body), markers of the liver (alanine transaminase [ALT], aspartate aminotransferase [AST], and gamma-glutamyl transferase [GGT]) and kidney (creatinine and urea) function, and lipid profile (low-density lipoprotein [LDL], high-density lipoprotein [HDL], and cholesterol levels in a cohort of healthy, untrained older ex-military males. Methods: Forty healthy untrained older ex-military males (age: 61 ± 2 yr, body mass index: 23.2 ± 1.3 kg.m-2) performed 8 weeks (three sessions·w−1) of RT with either 1.6 g/kg/d (RHP; n = 20) or 0.8 g/kg/d of protein (RLP; n = 20). Body composition (assessed by Inbody 720), muscular strength (1-RM for chest and leg press), power (Wingate test), endurance (75% 1-RM for chest and leg press), and markers of liver and kidney function (biochemical kits) were assessed pre and post-intervention. Results: SMM and muscular strength (upper and lower body) increased post-intervention in both groups and were significantly greater in RHP compared to RLP, while muscular power increased to the same extent in both groups (p<0.05) with no between-group differences (p>0.05). In contrast, there were no post-intervention changes in muscular endurance, HDL, and BFP remained in either group (p>0.05). ALT and creatinine significantly increased in RHP compared to RLP while GGT, AST, and urea only increased in the RLP group (p<0.05). LDL and cholesterol significantly decreased in both groups (p<0.05). Conclusion: A daily intake of 1.6 g/kg/d protein was superior to 0.8 g/kg/d (current recommended daily intake) for promoting greater improvements in SMM and muscle strength and thus may be a more suitable level of intake for promoting such adaptive responses. Notwithstanding observed between-group differences in ALT and creatinine and the fact that levels remained within normal ranges, it is feasible to conclude that this daily protein intake is efficacious and well tolerated by healthy, untrained older ex-military males.